(untitled) (Journal of Pathology of Nepal, 2019)
Background: Breast diseases are more common in women than men. Breasts undergo perpetual physical and physiological transition from puberty till death, which are related to menstruation, pregnancy, and menopause. The aim of this was to classify different types of the breast lesions, and conduct its clinicopathological study. Materials and Methods: Breast lesion tissue specimens were collected either as needle biopsy, lumpectomy, or mastectomy. For specimens fixation, 10% formal saline was used. Tissue was processed into paraffin blocks and stained using hematoxylin and eosin. Data were entered into Microsoft Excel spreadsheets and analyzed using percentages. Results: Out of 150 patients, 97.3% were female and 2.7% were male. Nonneoplastic lesions and neoplastic lesions accounted for 11% and 89% of the cases in patients, respectively. Among the nonneoplastic lesions, chronic mastitis (47%) was most common. Fibroadenoma (76%) and invasive ductal carcinoma (91%) was the highest encountered benign and malignant neoplasm, respectively. Maximum (43%) of benign neoplasm incidence was encountered in the age-group 20–30 years; whereas in malignant neoplasm, it was 40–50 years (38%). Out of 150 patients, 55% were diagnosed with Nottingham grading system grade 2 of breast cancer. Conclusions: Occurrence of neoplastic lesions in the breasts is comparatively higher than nonneoplastic lesions. Differentiating between benign and malignant lesions would be useful in the management and treatment of patients.